DNA methylation analysis of NOTCH1 variants reveals the first episignature for non-syndromic congenital heart defects - Dombrowsky, Gregor; van der Laan, Liselot; Silva, Ananília; Breckpot, Jeroen; Audain, Enrique; Wilsdon, Anna; Levy, Michael A.; Vos, Niels; Mannens, Marcel; Wang, Jiao; Jain, Anjali; Lesurf, Robert; et al. (Genome Medicine, 2026)
Background: Congenital heart defects (CHDs) are the most common malformation amongst newborns, with a prevalence of approximately 0.8–2%. The etiology of CHD is highly complex and can be linked to genetic and nongenetic factors. The molecular basis remains partially unclear, and only a minority of patients can be assigned to clear monogenic causes. Methods: Here we analyzed a cohort of 3907 CHD cases and population-matched controls using exome sequencing. In addition, we employed epigenetic profiling on a subset of cases that harbored rare NOTCH1 variants. Results: We identified 24 pathogenic or likely pathogenic single nucleotide variants (SNVs) in NOTCH1 in our exome cohort, as well as a further 15 variants of uncertain significance (VUS) likely to have a deleterious effect. Although the cardiac phenotypes showed some heterogeneity, non-syndromic Tetralogy of Fallot (ToF) and related malformations were the most frequent finding in 56% (22/39). In particular, missense variants altering cysteine residues involved in forming disulfide bridges were identified, specifically in TOF patients. Altogether, NOTCH1-haploinsufficiency represented the most common monogenic cause in our cohort and accounted for an estimated 1% of CHD cases. Combined with additional cases assembled through collaborations, we present 67 individuals with ultrarare variants affecting NOTCH1. This prominent role of NOTCH1 calls for an accurate and accessible evaluation of variants. To this end we explored DNA methylation testing and successfully established a NOTCH1-specific episignature. This signature also displays a robust specificity in relation to 99 other episignatures. Taken together, we found that truncating, splice-altering, as well as missense NOTCH1 variants, can generate a distinct DNAm episignature. Conclusions: We identified that NOTCH1-haploinsufficiency variants represented the most common monogenic cause in our cohort and accounted for an estimated 1 % of CHD cases. Furthermore, we conclude that methylation profiling can contribute to (NOTCH1) variant interpretation and improve the diagnostic management of CHD patients. Lastly, we established a NOTCH1-specific episignature, which represents the first non-syndromic signature, significantly extending the scope of patients that can benefit from methylation analysis.
CRIS-Team Scopus Importer:2026-01-23
Keywords: Congenital heart defects; Disulfide-bridges; DNA-methylation; Episignatures; NOTCH1; Tetralogy of Fallot